2013
DOI: 10.1128/aem.03138-13
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the Probiotic Enterococcus faecium Strain NCIMB 10415 to Piglets Specifically Reduces the Number of Escherichia coli Pathotypes That Adhere to the Gut Mucosa

Abstract: f Feed supplementation with the probiotic Enterococcus faecium for piglets has been found to reduce pathogenic gut microorganisms. Since Escherichia coli is among the most important pathogens in pig production, we performed comprehensive analyses to gain further insight into the influence of E. faecium NCIMB 10415 on porcine intestinal E. coli. A total of 1,436 E. coli strains were isolated from three intestinal habitats (mucosa, digesta, and feces) of probiotic-supplemented and nonsupplemented (control) pigle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 58 publications
4
56
0
1
Order By: Relevance
“…Strompfova et al (2006) did not find a lower number of E. coli in any part of the piglet intestines after administration of this probiotic. The results of Bednorz et al (2013) suggest a minor influence of E. faecium on the overall population of E. coli in healthy piglets but it has a profound effect on mucosa-adherent bacteria. The inhibitory effect of E. faecium found in this experiment was observed also by Szaboova et al (2008), who found a decrease of E. coli and Clostridium sp.…”
Section: Discussionmentioning
confidence: 86%
“…Strompfova et al (2006) did not find a lower number of E. coli in any part of the piglet intestines after administration of this probiotic. The results of Bednorz et al (2013) suggest a minor influence of E. faecium on the overall population of E. coli in healthy piglets but it has a profound effect on mucosa-adherent bacteria. The inhibitory effect of E. faecium found in this experiment was observed also by Szaboova et al (2008), who found a decrease of E. coli and Clostridium sp.…”
Section: Discussionmentioning
confidence: 86%
“…Investigations with infants fed Lactobacillus reported a reduced duration of diarrhea (5,6). Studies in pigs showed that Enterococcus faecium NCIMB 10415 reduced the number of mucosa-adherent Escherichia coli pathotypes (7) and that E. faecium reduces Chlamydia loads (8). Those data suggested a potential beneficial effect of the use of E. faecium as a probiotic to reduce infectious diseases.…”
mentioning
confidence: 74%
“…Intestinal microbial metabolites in ileum digesta 16 T 15 Intestinal microbial metabolites in colon digesta 16 T 16 Intestinal microbiota in stomach digesta 17 T 17 Intestinal microbiota in jejunum digesta 17 T 18 Intestinal microbiota in ileum digesta 17 T 19 Intestinal microbiota in colon digesta 17 T 20 Concentration of cytokines in blood 6 T 21 Gene expression in blood 3 T 22 Gene expression in ileum Peyer's patches 10 T 23 Gene expression in jejunum lymph nodes 7 T 24 Gene expression in jejunum Peyer's patches 10 T 25 Gene expression in liver tissue 2 T 26 Gene expression in spleen tissue 7 T 27 Abundance of lymphocytes in blood 33 T 28 Abundance of lymphocytes in ileum 9 T 29 Abundance of lymphocytes in ileum lymph nodes 16 T 30 Abundance of lymphocytes in ileum Peyer's patches…”
Section: T 14mentioning
confidence: 99%
“…p-values, given in brackets, were calculated by permutation tests. Jejunum gene expression 26 days 0.47 0.044 T 18 Intestinal microbiota in ileum digesta 34 days 0.40 0.022 T 22 Gene expression in ileum Peyer's patches 34 days 0.74 0.019 The microbial community in the ileum of 34 days old piglets was also significantly altered by the supplementation with E. faecium NCIMB 10415, as indicated by an enrichment score of ES(T 18 ) = 0.40 (p = 0.022). The target contained 17 variables where 10 variables showed an ANOVA p-value below 0.23 ( Figure 4C).…”
Section: Enrichment Analysismentioning
confidence: 99%
See 1 more Smart Citation